European Review of Contract Law (De Gruyter, 1967)
This journal deals with contract law and serves as a pan-European platform for discussion and analysis. Since the early 2000s when this journal was created, European Contract Law has come to encompass an increasingly comprehensive body of law. The importance and breadth of the field and the methods and questions involved are such that ERCL has established itself as the specialised European journal in this area.